Factors Influencing Entrepreneurs Choosing an Electronic Payment System in Mae Ka Sub-district, Phayao Province - Sittichai Leewiwatwong; Wanlop Lomtaku; Namfon Khamnual; Rattanawadee Samboon; Rujira Kamemongkon (Journal of Humanities and Social Sciences Mahasarakham University, 2022)
In this research, ed investigated the factors influencing an entrepreneur using an electronic payment system in Mae Kasub-district, Phayao province.Thedata was collected from 240 people using questionnaires. The statistical methods used for data analysis were frequency, percentage, mean, standard deviation, t-test and binary logic model. In this research, ed investigated the factors influencing an entrepreneur using an The results of the study showed that most of the respondents were married females, age 40-49 years old. They held an educational degree lower than a bachelor’s degree. Their monthly income was less than 15,000 baht. For the communication technology adoption factor, moof opinions were at high level. The factor, the most influenced entrepreneurs using electronic payment system was personal factor. From the analysis of results, the marital status was a personal factor influencing to entrepreneur using electronic payment systems at the significance level of 0.05. system in Mae Kasub-district, Phayaoprovince. Thedata was collected from 240 people using questionnaires. The statistical methods used for data analysis were frequency, percentage, mean, standard deviation, t-test and binary logic model.